Geometry of isoparametric null hypersurfaces of Lorentzian manifolds - Ssekajja, Samuel (My University, 2019)
We define two types of null hypersurfaces as; isoparametric and quasi isoparametric null hypersurfaces of Lorentzian space forms, based on the two shape operators associated with a null hypersurface. We prove that; on any screen conformal isoparametric null hypersurface, the screen geodesics lie on circles in the ambient space. Furthermore, we prove that the screen distributions of isoparametric (or quasi-parametric) null hypersurfaces with at most two principal curvatures are generally Riemannian products. Several examples are also given to illustrate the main concepts.
Keywords: Mathematics; Geometry and Topology; Physical Sciences and Mathematics